2015
DOI: 10.1515/zpch-2014-0632
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical Properties of Hydroxycyclohexadienyl Peroxy Isomers from Reaction of O2 with the Benzene-OH adduct

Abstract: Abstract:The addition of OH radical to benzene and other aromatic species to form a cyclohexadienyl radical (C•HD-OH), is the first step for conversion (oxidation) of aromatic species in atmospheric chemistry. Reaction of this C•HD-OH intermediate, with ground-state molecular oxygen forms a number of hydroxylcyclohexadienyl peroxy (CHD-OH-OO•) isomers, which further react to form aerosols. Ab initio and density functional calculations were used to study the structures and thermochemical properties (Δ o 298 , o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…The difference in IDT predictions at 900 K is about an order of magnitude. Using the higher entropy value from the QC calculations, the equilibrium shifts to form this radical which promotes reactivity, resulting in shorter predicted IDTs and Sebbar et al 20 10 hydroxycyclohexadienyl peroxy isomers Chen et al 21 11 C 1 −C 4 hydroperoxides and peroxy radicals Wang et al 22 12 alcohols, hydroperoxides, and vinylic, alkoxy, and alkylperoxy radicals Yommee et al 23 13 hydroxyl-and hydroperoxide-substituted furan, methylfuran, and methoxyfuran Hudzik et al 24 14 isooctane and carbon radicals Snitsiriwat et al 25 better agreement with the experimental data. Further investigation found that, using the GA method, there are two different ways in which the thermochemistry of 2-propenyl-1methyl radical can be calculated, as shown in Figure 4 and Table 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in IDT predictions at 900 K is about an order of magnitude. Using the higher entropy value from the QC calculations, the equilibrium shifts to form this radical which promotes reactivity, resulting in shorter predicted IDTs and Sebbar et al 20 10 hydroxycyclohexadienyl peroxy isomers Chen et al 21 11 C 1 −C 4 hydroperoxides and peroxy radicals Wang et al 22 12 alcohols, hydroperoxides, and vinylic, alkoxy, and alkylperoxy radicals Yommee et al 23 13 hydroxyl-and hydroperoxide-substituted furan, methylfuran, and methoxyfuran Hudzik et al 24 14 isooctane and carbon radicals Snitsiriwat et al 25 better agreement with the experimental data. Further investigation found that, using the GA method, there are two different ways in which the thermochemistry of 2-propenyl-1methyl radical can be calculated, as shown in Figure 4 and Table 2.…”
Section: Introductionmentioning
confidence: 99%
“…Ritter and Bozzelli developed THERM (THermo Estimation for Radicals and Molecules) based on Benson’s GA method, which can be used as illustrated in Figure . Bozzelli and co-workers have also studied the thermochemistry of different classes of species including sulfurated, nitridated, fluorinated, oxygenated, and saturated hydrocarbons, Table . Enthalpies of formation, entropies, and heat capacities have been compiled for certain classes of species using density functional theory (DFT) and composite compound methods, from which bond dissociation energies (BDEs) of similar type of bonds and GAVs were systematically reported and compared.…”
Section: Introductionmentioning
confidence: 99%
“…Goldsmith et al [17] database consists of 219 small molecules that are relevant in combustion chemistry, including species with different electronic configurations such as radicals and biradicals. There are several other works that published accurate thermochemistry data for species of interest in combustion by means of electronic structure calculations [2,3,[21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%